Bazi Bushen ameliorates age-related energy metabolism dysregulation by targeting the IL-17/TNF inflammatory pathway associated with SASP - Shen, Xiaogang; Li, Mengnan; Li, Yawen; Jiang, Yuning; Niu, Kunxu; Zhang, Shixiong; Lu, Xuan; Zhang, Runtao; Zhao, Zhiqin; Zhou, Liangxing; Guo, Zhifang; Wang, Siwei; et al. (Chinese medicine, 2024)
Background Chronic inflammation and metabolic dysfunction are key features of systemic aging, closely associated with the development and progression of age-related metabolic diseases. Bazi Bushen (BZBS), a traditional Chinese medicine used to alleviate frailty, delays biological aging by modulating DNA methylation levels. However, the precise mechanism of its anti-aging effect remains unclear. In this study, we developed the Energy Expenditure Aging Index (EEAI) to estimate biological age. By integrating the EEAI with transcriptome analysis, we aimed to explore the impact of BZBS on age-related metabolic dysregulation and inflammation in naturally aging mice. Methods We conducted indirect calorimetry analysis on five groups of mice with different ages and utilized the data to construct EEAI. 12 -month-old C57BL/6 J mice were treated with BZBS or β-Nicotinamide Mononucleotide (NMN) for 8 months. Micro-CT, Oil Red O staining, indirect calorimetry, RNA sequencing, bioinformatics analysis, and qRT-PCR were performed to investigate the regulatory effects of BZBS on energy metabolism, glycolipid metabolism, and inflammaging. Results The results revealed that BZBS treatment effectively reversed the age-related decline in energy expenditure and enhanced overall metabolism, as indicated by the aging index of energy expenditure derived from energy metabolism parameters across various ages. Subsequent investigations showed that BZBS reduced age-induced visceral fat accumulation and hepatic lipid droplet aggregation. Transcriptomic analysis of perirenal fat and liver indicated that BZBS effectively enhanced lipid metabolism pathways, such as the PPAR signaling pathway, fatty acid oxidation, and cholesterol metabolism, and improved glycolysis and mitochondrial respiration. Additionally, there was a significant improvement in inhibiting the inflammation-related arachidonic acid-linoleic acid metabolism pathway and restraining the IL-17 and TNF inflammatory pathways activated via senescence associated secretory phenotype (SASP). Conclusions BZBS has the potential to alleviate inflammation in metabolic organs of naturally aged mice and maintain metabolic homeostasis. This study presents novel clinical therapeutic approaches for the prevention and treatment of age-related metabolic diseases.